Antibiotic resistance patterns of Staphylococcus aureus: A multi center study from India. (September 2016) - Mendem, Suresh Kumar; Alasthimannahalli Gangadhara, Triveni; Shivannavar, Channappa T.; Gaddad, Subhaschandra M.
Abstract: Chemotherapy and emergence of drug resistance strains of Staphylococcus aureus is receiving serious threats, due to the origin and spread of hospital and community acquired MDR strains. The present study reports the prevalence of antibiotic resistance among Staphylococcus aureus isolated from clinical samples from different cities of India. Antibiotic sensitivity was performed by Kirby-Bauer disk diffusion method and minimum inhibitory concentrations were determined for vancomycin and methicillin according to CLSI (2014) guidelines. A total of 212 S . aureus were obtained from different samples such as pus, blood, urine. The antibiogram of these isolates indicated widespread resistance to various groups of antibiotics ranging from a minimum of 10.13% against Phenicols (Chloramphenicol) to a maximum of 97% against Penicillin and 44.8% isolates were MRSA and alarmingly 10.84% were VRSA. Most of the MRSA isolates showed inducible Clindamycin resistance. Widespread prevalence of MDR patterns, increasing incidence of MRSA and VRSA calls for exploration of alternative medicines and new approaches to combat Staphylococcal infections. Graphical abstract: Highlights: Staphylococcus aureus is emerging pathogen. Incidence of MDR stains reported from various regions of India. Prevalence of MRSA and VRSA high in immunocompromised patients and chronic UTI infections. Most of the MRSA Strains also showing inducible clindamycin resistance. Linezolid, cephalosporins and macrolides are showing increasing resistance patterns among MRSA infections. Consistent efforts are necessary to prevent and monitor the emergence of MDR S . aureus .